2012
DOI: 10.1603/ec11287
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Detoxification Enzymes by Quercetin in the Silkworm

Abstract: Quercetin is one of the most abundant flavonoids and the defense secondary metabolites in plants. In this study, the effect of quercetin on the growth of the silkworm larvae was investigated. Cytochrome P450 monooxygenases (P450s), glutathione S-transferases (GSTs), and carboxylesterases (COE) were assayed after exposure to different concentrations of quercetin for 3 d (short-term) and 7 d (long-term), respectively. The results showed that the weight gain of the silkworm larvae significantly decreased after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…Epsilon group members, particularly ApGST-E1 and ApGST-E3 showed peak mRNA levels in the midgut tissue wherein they might be participating in metabolizing dietary toxins ingested from the host plant. Several studies of plant-insect interaction have shown the midgut tissue as the major interface for several detoxification enzymes including GSTs (Hakim et al, 2010;Mittapalli et al, 2010;Pauchet et al, 2010;Rajarapu et al, 2011;Zhang et al, 2012). ApGST-E2 was also high in Malpighian tubules, an important physiological (renal) tissue that is vital in eliminating dietary toxins as reported in other insects (Chahine and O'Donnell, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…Epsilon group members, particularly ApGST-E1 and ApGST-E3 showed peak mRNA levels in the midgut tissue wherein they might be participating in metabolizing dietary toxins ingested from the host plant. Several studies of plant-insect interaction have shown the midgut tissue as the major interface for several detoxification enzymes including GSTs (Hakim et al, 2010;Mittapalli et al, 2010;Pauchet et al, 2010;Rajarapu et al, 2011;Zhang et al, 2012). ApGST-E2 was also high in Malpighian tubules, an important physiological (renal) tissue that is vital in eliminating dietary toxins as reported in other insects (Chahine and O'Donnell, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…In many cases, gene amplification following an exposure to xenobiotic compounds enhances expression levels of metabolic enzymes that in turn triggers resistance. Examples of induction of CarEs by xenobiotics are reported by Yu, and Zhang et al, .…”
Section: Introductionmentioning
confidence: 87%
“…In many cases, gene amplification following an exposure to xenobiotic compounds enhances expression levels of metabolic enzymes that in turn triggers resistance. Examples of induction of CarEs by xenobiotics are reported by Yu, 2004 andZhang et al, 2012. Beside the detoxification, CarEs are involved in other insects physiological processes including regulation of the growth and development. It has been shown that the r 215 expression patterns of CarE genes vary during different developmental stages and different sexes suggesting possible functional roles of the CarE genes (Campbell et al, 2003;Mujeeb and Shakoori, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…3) In this study, oriental armyworm Mythimna separata larvae were fed artificial diets containing 1% quercetin to investigate how M. separata larvae would cope with the toxic compound. The metabolism of quercetin in insects is still unclear and requires further investigation, although quercetin 5-O-glucoside has been identified from orally administrated quercetin in the Bombyx mori silkworm.…”
Section: )mentioning
confidence: 99%